Precipitation behaviour and mechanical properties of a novel Al0.5MoTaTi complex concentrated alloy. (December 2019) - Schliephake, Daniel; Medvedev, Alexander E.; Imran, Mohammad K.; Obert, Susanne; Fabijanic, Daniel; Heilmaier, Martin; Molotnikov, Andrey; Wu, Xinhua
Abstract: The precipitation behaviour in a novel Al0.5 MoTaTi complex concentrated alloy (CCA) is described in this study. The alloy was fabricated through an arc-melting process. Solution heat treatment and additional aging was performed at 1673 K and 1273 K, respectively. It was found, that a disordered body-centred cubic phase (bcc) precipitates in cuboidal- and loop-shaped form within an ordered B2 phase. The mechanism of the formation of the loops is believed to be related to the transformation of anti-phase boundaries (APB) in the ordered B2 phase at high temperatures, which act as nucleation sites for the disordered bcc phase during cooling and aging. Graphical abstract: Unlabelled Image